Effect of acupuncture on endometrial receptivity in women with thin endometrium: study protocol for a single-centre, randomised, sham-controlled trial - Xin Liu; Li Yang; Xiaoyan Wang; Huanfang Xu; Yigong Fang; Pengfei Du; Chenchen Su; Jiashan Li; Weixin Li; Tian Hang; Yaoyao Zhu (BMJ Open, 2025)
Introduction Thin endometrium poses a major therapeutic challenge in assisted reproductive technologies by compromising pregnancy success and live birth outcomes. A substantial proportion of patients remain refractory to existing therapies. Preliminary evidence suggests acupuncture may improve endometrial thickness (EMT). This study aims to assess the effect of acupuncture against sham acupuncture for women with thin endometrium.Methods and analysis This study is a single-centre, randomised, sham-controlled trial conducted at a specialised acupuncture hospital in Beijing, China. A total of 120 women with thin endometrium will be randomised (1:1) to receive 36 sessions of acupuncture or sham acupuncture over 12 weeks. The primary outcome is the EMT at week 12. Secondary outcomes are endometrial pattern, uterine arterial blood flow parameters (Pulsatility Index, Resistance Index and the ratio of peak systolic to end-diastolic blood flow velocities), endometrium blood flow, serum oestradiol concentration, clinical pregnancy rate and Self-Rating Anxiety Scale Scores.Ethics and dissemination This study has been approved by the ethics committee of the Institute of Acupuncture and Moxibustion, China Academy of Chinese Medical Sciences (approval no.: S2024-04-23-1). Each participant will be required to provide written informed consent before enrolment. Findings will be disseminated through peer-reviewed publications and conference presentations.Trial registration number ITMCTR2024000053.